Koi Fish (Cyprinus carpio) Nursery Techniques at the Batu Kumbung Lingsar Fish Seed Center, West Lombok - Murtiningsih, Sustanti; Setyono, Bagus Dwi Hari (Journal of Fish Health, 2023)
Koi fish is one type of freshwater fish that is classified as an ornamental freshwater fish that has economic value in the national and international markets. Efforts to develop koi fish cultivation cannot be separated from the breeding stage such as enlargement and nursery activities. One of the koi fish cultivation places in West Lombok Regency is at the Batu Kumbung Lingsar Fish Seed Center, so it is necessary to know what nursery techniques are applied there considering its good production. The activity was carried out for approximately 30 days at the Batu Kumbung Lingsar using a descriptive method. The results of the activities obtained were that in the koi fish nursery technique at the Batu Kumbung Lingsar Fish Seed Center, it started from pond preparation (drying, fertilization, liming, filling with water), parent selection, spawning, nursery and feeding. The pond drying is done for 2 days, liming, fertilization, and filling with water are done for 1 day, the weight of the parent that is ready to spawn is 1.5 kg for the male parent while for the female parent 4 kg, the ratio of the parent used is 2:1 where 6 male and 3 female broodstocks, the nursery is done at the age of 2 days with the results of the offspring spread in the nursery as many as 5000 larvae, and the feeding technique uses the ad satiation method.